The role of chondrocyte-to-osteoblast trans-differentiation in fetal bone dysplasia of mice caused by prenatal exposure to dexamethasone - Zhu, Jiayong; Zhao, Xiaoqi; Wang, Hui; Xiao, Hao; Chen, Liaobin (Frontiers in Pharmacology, 2023)
Maternal exposure to dexamethasone can cause developmental toxicity of long bones in offspring. However, the effect of dexamethasone on the trans-differentiation of growth plate chondrocytes into osteoblasts and its role in bone dysplasia of fetuses caused by prenatal dexamethasone exposure (PDE) remains unclear. In this study, pregnant mice were treated with different doses, stages, and courses of dexamethasone according to clinical practice to reveal the phenomenon. Further, growth plate chondrocytes were treated with dexamethasone in vitro to clarify the phenomenon and mechanism. The results showed that PDE caused dysplasia of fetal long bones in female and male mice, accompanied by the delayed formation of the primary ossification center and the widening hypertrophic zone of growth plate cartilage. Meanwhile, PDE increased the number of hypertrophic chondrocytes at growth plate cartilage and decreased the number of osteoblasts at the primary ossification center. Moreover, PDE significantly decreased the expression of osteogenic transcription factor Runx2 but increased the expression of hypertrophic chondrocytes marker Col10. These above phenomena were more significant in the high dose, early stage, and double courses of dexamethasone exposure groups, and the male fetal mice showed more obvious than the female fetal mice. In vitro, dexamethasone significantly inhibited the trans-differentiation of growth plate chondrocytes into osteoblasts, accompanied by a decrease in Runx2 expression and an increase in Col10 expression. In conclusion, this study revealed the phenomenon and mechanism of fetal bone dysplasia caused by PDE from the new perspective of trans-differentiation disorder of growth plate chondrocytes to osteoblasts.